2009
DOI: 10.1021/ja9053948
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Decarboxylative Asymmetric Allylic Alkylation of Enol Carbonates

Abstract: Palladium-catalyzed decarboxylative asymmetric allylic alkylation (DAAA) of allyl enol carbonates as a highly chemo-, regio-and enantio-selective process for the synthesis of ketones bearing either a quaternary or a tertiary α-stereogenic center has been investigated in detail. Chiral ligand L4 was found to be optimal in the DAAA of a broad scope of cyclic and acyclic ketones including simple aliphatic ketones with more than one enolizable proton. The allyl moiety of the carbonates has been extended to a varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
149
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 286 publications
(156 citation statements)
references
References 90 publications
3
149
0
4
Order By: Relevance
“…68 Initial studies showed that allylation of cyclic ketones to form both tertiary (eq 66) and quaternary (eq 67) centers works well. 69 The ligand of choice is that which has the largest bite angle, the anthracenyl derived one L A . Acyclic substrates work equally well.…”
Section: Enantioselectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…68 Initial studies showed that allylation of cyclic ketones to form both tertiary (eq 66) and quaternary (eq 67) centers works well. 69 The ligand of choice is that which has the largest bite angle, the anthracenyl derived one L A . Acyclic substrates work equally well.…”
Section: Enantioselectivitymentioning
confidence: 99%
“…Acyclic substrates work equally well. 69,70 Enolate geometry controls facial selectivity as shown in eq 68 and 69 wherein switching from a Z to an E enolate inverts the stereochemistry of the newly formed stereocenter. No enolate equilibration occurs nor does any polyalkylation.…”
Section: Enantioselectivitymentioning
confidence: 99%
“…[33] While good yields were be obtained, the ee was too low to be useful, even when the ANDEN ligand 36 was used (Table 2). [34] Thus, the acyl oxazolidinone allylation route remains the most effective route to this series of compounds. …”
Section: Synthesis Of 2-methyl-but-3-enyl Derivativesmentioning
confidence: 99%
“…A noteworthy discovery was made during a study by Trost [33]: the base used in the generation of the nucleophile was found to influence the overall allylic alkylation (Table 3). The originally proposed mechanism suggests that in the case of an enolate obtained with Cs 2 CO 3 as base, the Si face attack generates less steric hindrance than the Re face attack.…”
Section: Trost's Ligandsmentioning
confidence: 99%
“…For example, L5 is a very powerful ligand for the palladium-catalyzed decarboxylative asymmetric allylic substitution (DAAS) of enol carbonates 12 (Scheme 10). It afforded the desired product 13 without the formation of the corresponding unsubstituted ketone 14 by simple decarboxylation [33].…”
Section: Trost's Ligandsmentioning
confidence: 99%